Optical microresonator arrays of fluorescence-switchable diarylethenes with unreplicable spectral fingerprints. Issue 7 (20th May 2020) - Okada, Daichi; Lin, Zhan-Hong; Huang, Jer-Shing; Oki, Osamu; Morimoto, Masakazu; Liu, Xuying; Minari, Takeo; Ishii, Satoshi; Nagao, Tadaaki; Irie, Masahiro; Yamamoto, Yohei
Abstract : Photochromic microresonator arrays with whispering gallery mode fingerprints are successfully prepared, which function as high-security optical authentication microdevices. Abstract : High-security identification requires authentication that is hard to counterfeit and replicate. For anti-counterfeiting data storage and rewritable memory devices, chromic materials are adoptable, where the dichromatic colours can be switched by external stimuli. If further individual information is embedded in each pixel, a much higher-level security system beyond the zero/one data array will be realized. For this purpose, a fine whispering gallery mode (WGM) fingerprint pattern from a microresonator is applicable. Here we propose that photoswitchable optical microresonators made of a fluorescent photochromic organic material function as anti-counterfeiting, rewritable optical memories. The WGM photoluminescence of the resultant microspheres can be switched on and off repeatedly by irradiation with ultraviolet and visible light. The shape of the microresonator varies from a sphere to an oblate ellipsoid and hemisphere, depending on the self-assembly process, and the WGM spectral pattern depends sensitively on the morphology of the resonators. Furthermore, surface self-assembly on a hydrophobic/hydrophilic micropatterned substrate affords a highly integrated array of microresonators as dense as millions of pixels per square centimetre. The spectral fingerprints of all pixels are different from one another; therefore, the photoswitchable microarrays are applicable as an ultimate anti-counterfeiting system which is hard to replicate.